Teaching Students with Disabilities: Autism Spectrum Disorder and Asperger's Syndrome - Sarah E. LaRose; Andrew C. Thoron (EDIS)
Teachers of all subjects must familiarize themselves with the specific needs of the students in their classrooms, especially in the case of students with autism spectrum disorders (ASD) and Asperger’s syndrome because students may vary greatly in the degree to which they are affected by these disabilities. This 4-page fact sheet explains the differences between autism and Asperger’s syndrome and how instructors can modify their lessons to effectively meet the needs of learners with these disabilities in different types of learning environments and achieve greater classroom success for the educator and the learner. Written by Sara E. LaRose and Andrew C. Thoron, and published by the Agricultural Education and Communication Department, December 2015.